How economics helped shape American Judaism - Carmel Ullman Chiswick (Institute for the Study of Labor (IZA), 2010)
This chapter discusses the strong impact of economic forces, and changes in the economic environment, on American Jewish observance and American Jewish religious institutions in the 20th century. Beginning with the immigrants' experience of dramatic economic change between the old country and the new, it focuses on how this affected differences between European and American Jewish practices during the first half of the twentieth century. Equally dramatic upward economic mobility had implications for additional changes during the second half of the century. These were manifested by the development of distinctively American patterns of Jewish education. The relationship between Jewish education in the United States and the other major branches of World Jewry is discussed from an economic perspective. The economic underpinnings of religious intermarriage and assimilation are reviewed. A concluding section forecasts the future of American Judaism and Jewish observance in the coming decades.
Keywords: Z12; N32; J12; 330; economics; religion; Judaism; economic history; immigrant adjustment; education; intermarriage; Juden; Migranten; Soziale Integration; Judentum; Wirtschaftsgeschichte; Bildungsökonomik; Ethnische Beziehungen; Ehe; USA